Teacher's followership model in Philippines basic education implications on leadership and organizational development - Juarez, Ana Maria Concepcion R.
In the Philippines, there has been little effort to look into followership, the other half of the leadership equation. With the decentralization thrust in basic education, understanding the followership of teachers is even more crucial as this has to do with their roles as subordinates in the organization. This study addresses this gap by constructing a model that describes the followership of teachers in a Philippines context. In-depth interview with 10 basic education teachers from Luzon, Visayas, and Mindanao were conducted and analyzed, employing Constructivist Grounded Theory method. The model describes followership of teachers according to the characteristics (limited power, less pressure, respect for authority), behavior (obedience, dutifulness, taking on extra work, and being uncomplaining), and motivations (upbringing, believing in a greater purpose, social support, and future plans). It also details what followers consider ideal and problematic leader characteristics. The model reveals that the followership of teachers in a Philippines context is passive in orientation. Followers see their role as inferior to their leader, in terms of rank but also in terms of significance. This inferiority leads the followers to questions their right to a voice, to make suggestions, or to make demands. Followership was found to be highly dependent upon the kind of leadership in the organization. Contextual factors such as upbringing, religion, and personal values shape the followership of teachers. Implications for leadership and organizational policies, practice, and research are discussed.